2015
DOI: 10.1016/j.celrep.2015.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Grass Plants Bind, Retain, Uptake, and Transport Infectious Prions

Abstract: Prions are the protein-based infectious agents responsible for prion diseases. Environmental prion contamination has been implicated in disease transmission. Here we analyzed the binding and retention of infectious prion protein (PrPSc) to plants. Small quantities of PrPSc contained in diluted brain homogenate or in excretory materials (urine and feces) can bind to wheat grass roots and leaves. Wild type hamsters were efficiently infected by ingestion of prion-contaminated plants. The prion-plant interaction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
94
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 34 publications
3
94
0
2
Order By: Relevance
“…to assess the potential for infectivity in body fluids and other excreta (19,74,78,79), and to detect low levels of misfolded protein in soil (80), water (81), and plant samples (82). Notably, the CWD seeds generated in vitro by sPMCA have proven infectious to some degree in susceptible hosts (83), indicating that the technique may accurately model what occurs in vivo; therein lays its advantage among amplification strategies.…”
Section: Protein Misfolding Cyclic Amplificationmentioning
confidence: 99%
“…to assess the potential for infectivity in body fluids and other excreta (19,74,78,79), and to detect low levels of misfolded protein in soil (80), water (81), and plant samples (82). Notably, the CWD seeds generated in vitro by sPMCA have proven infectious to some degree in susceptible hosts (83), indicating that the technique may accurately model what occurs in vivo; therein lays its advantage among amplification strategies.…”
Section: Protein Misfolding Cyclic Amplificationmentioning
confidence: 99%
“…This article is available in: http://headache.imedpub.com/ even translocation of prions within plants, there may be a positive pressure to maintain this disease in a geographic area [12].…”
Section: Journal Of Headache and Pain Management Issn 2472-1913mentioning
confidence: 99%
“…Prions are highly resistant to degradation and have been shown to exist in soil for years [1]. Recent studies have reported these agents can bind and be taken up by plants [12]. Further, infectivity can be spread when animals consume contaminated plant material.…”
Section: Journal Of Headache and Pain Management Issn 2472-1913mentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental contamination with CWD infectivity in excreta or decomposing carcasses contributes to horizontal transmission of CWD in mule deer (10). Prion infectivity has been shown to persist on the surface of contaminated plant leaves and roots (36) and in soil (37)(38)(39). Therefore, feral pigs could be exposed to infectivity through scavenging of CWD-affected carcasses, by consumption of contaminated vegetation, and while rooting around in the soil during foraging.…”
mentioning
confidence: 99%